Unusual rebuilding method of historic St Mary`s cathedral in the capital of Western Australia = Nietypowy sposób przebudowy zabytkowej katedry St Mary w stolicy Zachodniej Australii - Wysokowski, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
St Mary`s Cathedral is the Archbishop church of the Archdiocese in Perth in Western Australia. The presented sacral building was built in neo-Gothic style during the years 1863-1865. Cathedral was officially dedicated and opened for the service on 29th January, 1865. In 1973 was proclaimed the Marian Sanctuary and now represents one of the largest religious facilities in Perth. In 2005, the city authorities, together with the Archdiocese took a collective decision on the necessity of a comprehensive renovation of this sacred object. The renovation was due to the technical condition and the lack of usability of the object.
Keywords: obiekt sakralny; rewitalizacja; przebudowa; funkcjonalność; cechy techniczno-użytkowe; cathedral; historical facilities; rebuilding; renovation; functionality